The effect of distance learning on student learning achievement: a meta-analysis - Nusantara, Bayuk; Hadi, Samsul; Retnawati, Heri; Sumaryanto, Sumaryanto; Prasojo, Lantip Diat; Sotlikova, Rimajon; Arlinwibowo, Janu (International Journal of Electrical and Computer Engineering (IJECE), 2024)
Distance learning has been an option during the last few years due to the coronavirus disease 2019 (COVID-19) pandemic. The aim of this research is to identify the effectiveness of distance learning compared to conventional learning in terms of student learning achievement. This research is meta- analysis of random group contrast design (experiment-control) models. The data selection process refers to the inclusion criteria of year, theme, data type and data completeness. Based on these criteria, 10 articles were selected. The analysis process begins with testing the homogeneity assumption using three methods, namely ????2, ????2, and Q which shows heterogeneous data so that random model selection is appropriate, testing freedom of publication bias with Egger's test and funnel plot which shows that the data collected is free from publication bias, identifying the effect size and standard error, as well as conducting moderator variable analysis which considers domain, continent, subject, education level and year variables. The results of this study show that although distance learning has a positive influence on student learning achievement, the difference is not significant when compared with conventional learning. In addition, these results can be moderated by achievement domain variables, type of subject, level of education, and year.